Current Drug Managements of Wilson’s Disease: From West to East - Li, Wen-Jie; Chen, Chen; You, Zhi-Fei; Yang, Ren-Min; Wang, Xiao-Ping (Current Neuropharmacology, 2016)
Wilson’s disease (WD), also called hepatolenticular degeneration, is an autosomal recessive inheritance disorder of copper metabolism characterized by the multiple mutations in the ATP-ase 7B gene of chromosome 13q. About half of the WD patients have neurological or psychiatric symptoms. As WD is a kind of medicable or nearly curable neurodegenerative disease in the field of medicine, early consideration/examination and without delay/ life-long treatment usually lead to better prognoses. The drugs, also named as anticopper agents, are commonly used in clinics including D-penicillamine, trientine, sodium dimercaptosuccinate, dimercaptosuccinic acid, zinc and tetrathiomolybdate. This provides detailed reviews about these medicines.
Keywords: dimercaptosuccinic acid